2020
DOI: 10.1007/s12671-020-01514-3
|View full text |Cite
|
Sign up to set email alerts
|

The (non)Protective Role of Self-Compassion in Internalizing Symptoms: Two Empirical Studies in Adolescents Demonstrating Unwanted Effects of Using the Self-Compassion Scale Total Score

Abstract: Objectives Several scholars have questioned the use of the total Self-Compassion Scale (SCS) score as an appropriate index for measuring self-compassion as a protective psychological trait. Methods We present two new studies to further examine the relationships between SCS or SCS-Short Form scores and symptoms of anxiety and depression in non-clinical samples of adolescents (Ns being 106 and 52). Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 55 publications
4
17
0
Order By: Relevance
“…Moreover, we found a non-significant moderation effect of overall SC in the association between perceived discrimination and psychological distress. This finding echoes those of previous studies in which the inclusion of RUS in overall SC was found to inflate the relation between self-compassion and psychological distress, thus inhibiting the investigation of the protective function of self-compassion and its unique contribution in a psychopathological context (Muris et al, 2021). RUS might obscure the buffering effect of CS if it is added to CS to form an overall self-compassion (e.g., as a sum or average score on the SCS).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Moreover, we found a non-significant moderation effect of overall SC in the association between perceived discrimination and psychological distress. This finding echoes those of previous studies in which the inclusion of RUS in overall SC was found to inflate the relation between self-compassion and psychological distress, thus inhibiting the investigation of the protective function of self-compassion and its unique contribution in a psychopathological context (Muris et al, 2021). RUS might obscure the buffering effect of CS if it is added to CS to form an overall self-compassion (e.g., as a sum or average score on the SCS).…”
Section: Discussionsupporting
confidence: 84%
“…Specifically, CS was found to have played a moderating role in this association among socioeconomically disadvantaged emerging adults with a longitudinal design. This suggests that when researchers investigate the moderation effect of self-compassion within the domains of psychopathology (e.g., depression, anxiety, stress, rumination, negative affect) or in the stressorpsychological distress link, CS may be better than overall SC (total or average SCS score) in presenting a protective nature (Muris et al, 2021). If total or average SCS score is used, post hoc sensitivity analyses with additional moderation models are necessary to examine whether there are different moderating effects of CS and overall SC (Sick et al, 2020), especially in the context of psychopathology.…”
Section: Discussionmentioning
confidence: 99%
“…A total score of the SCS or the SCS-SF, which can be calculated by summing the three positive components (i.e., self-kindness, common humanity, and mindfulness) and the reversed scores of the three negative components (i.e., self-judgment, isolation, and over-identification), is intended to measure an overall construct of self-compassion (Hayes et al, 2016;Neff, 2016). In line with the original conceptualization of self-compassion (Neff, 2003b), most previous empirical research regarded self-compassion as a wholistic concept by using a total score composite as an overall measure of self-compassion, and relatively few researchers looked at the SCS components (Macbeth & Gumley, 2012;Muris et al, 2021). However, more recently, research has shown that positive components and negative components seem to be two distinct constructs, namely positive self-compassion and self-coldness (López et al, 2015;Muris & Petrocchi, 2016;Muris et al, 2018).…”
mentioning
confidence: 99%
“…In line with research including older adolescents and adults, self-compassion was associated with positive psychological constructs which have previously been identified in the extant literature. This includes resilience (Neff & McGehee, 2010;Trompetter et al, 2017) and optimism (Muris et al, 2020;Shapira & Mongrain, 2010). Self-compassion was negatively associated with other constructs identified in the literature including depression (Barlow et al, 2017;Lathren et al, 2019;Raes, 2011) and neuroticism (Pyszkowska, 2020).…”
Section: Discussionmentioning
confidence: 96%